2010
DOI: 10.1038/ncomms1125
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional imaging of magnetic domains

Abstract: magnetic domains have been the subject of much scientific investigation since their theoretical existence was first postulated by P.-E. Weiss over a century ago. up to now, the threedimensional (3D) domain structure of bulk magnets has never been observed owing to the lack of appropriate experimental methods. Domain analysis in bulk matter thus remains one of the most challenging tasks in research on magnetic materials. All current domain observation methods are limited to studying surface domains or thin magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
118
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(120 citation statements)
references
References 28 publications
0
118
0
2
Order By: Relevance
“…[1][2][3][4][5][6] The ideal form of magnetic microscopy will offer high spatial resolution, high temporal resolution, and high sensitivity to magnetization, magnetic moment, or magnetic field. It is also desirable that the technique should be nondestructive, nonperturbing, rapid, and affordable.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] The ideal form of magnetic microscopy will offer high spatial resolution, high temporal resolution, and high sensitivity to magnetization, magnetic moment, or magnetic field. It is also desirable that the technique should be nondestructive, nonperturbing, rapid, and affordable.…”
Section: Introductionmentioning
confidence: 99%
“…Grating interferometry with neutrons has proven particularly useful to detect magnetic domain walls and visualize magnetic domains even in the bulk of samples, which are not accessed by any other technique [18][19][20][21][22][23][24][25][26][27][28][29]. The Talbot-Lau grating interferometer, being the current standard in neutron grating interferometry consists of a set of three gratings ( Figure 3).…”
Section: Neutron Grating Interferometry (Ngi)mentioning
confidence: 99%
“…Microstructural deviations hence provided additional image contrast from structures beyond direct real space resolution, and contrast for material compositions, which would otherwise not provide contrast in terms of attenuation. In neutron imaging the detection of magnetic structures providing a signal due to splitting of the spin states of an unpolarized beam became most prominent [18][19][20][21][22][23][24][25][26][27][28][29]. However, also the detection of regions with altered porosity or precipitations in particular in metallic samples has been demonstrated and applied [40,41] (Figure 4).…”
Section: Modulated Beam Dark-field Contrast Theorymentioning
confidence: 99%
“…In contrast to this, a neutron grating interferometry setup is optimised to a specific wavelength, because of the wavelength dependency of the fractional Talbot distance as well as the induced phase shift in the phase gratings. 7,11 Therefore, although it has been shown that contrast can still be achieved over a range of a few angstroms, 12 the grating interferometry setup is generally not well suited for ToF applications, in particular with respect to a significant range to be probed efficiently.…”
Section: -2 Sales Et Almentioning
confidence: 99%